Strengthening Local Fiscal Capacity through Effective BPHTB Tax Collection - M. Zidny Nafi' Hasbi (International Journal of Economics Business and Social Sciences, 2026)
Local fiscal capacity plays a crucial role in supporting regional development and improving public service delivery. One of the important sources of local government revenue in many decentralized fiscal systems is the Land and Building Rights Acquisition Tax (BPHTB), which is imposed on the transfer of land and property ownership rights. Effective management and collection of BPHTB are therefore essential to strengthen local fiscal sustainability and enhance regional financial independence. This study aims to analyze how effective BPHTB tax collection contributes to strengthening local fiscal capacity. This research employs a quantitative and descriptive approach by examining various indicators related to tax administration, taxpayer compliance, and revenue performance. Data are obtained from official financial reports, tax administration records, and relevant government publications. The analysis focuses on evaluating the efficiency and effectiveness of BPHTB collection mechanisms, including administrative procedures, monitoring systems, and institutional capacity in managing local tax revenues.The findings indicate that effective BPHTB tax collection significantly contributes to increasing local government revenue and improving fiscal capacity. Efficient tax administration, improved taxpayer compliance, and the implementation of transparent and accountable tax management systems are key factors in enhancing BPHTB revenue performance.